Jóvenes, cultura escrita y tecno cultura: análisis de los resultados arrojados por la encuesta en una investigación sobre lectura, escritura, conocimiento y tecnocultura en la universidad (2005)
Parting from a conceptualization of what the written culture means and its importance over the educationalsystems during the Western Modernity, this article develops a hypothesis around the crisis of the writtenculture in our surroundings; and it brings forth empirical evidences provided by a survey on the 259students who had participated in the research over “Writing, knowledge, and techno-culture on campus.”The methodology includes a reading test and a writing test, the results of which were disclosed in anotherarticle. This one, on the other hand, analyses the survey that asked about the students’ socio-economicalclass, their reading and writing practices before and after being admitted to the university. It furthermoreinquired about the academic and extra-curricular spaces such practices provided; about the kinds ofsociability that favored their relationship with the written culture through reading and writing; it verifiedthe educational level of their parents, the usage of audiovisual means and new communication andinformation technologies (PC and internet), their interactions with them, and their ways of acquiring thoseknowledges that derive from their relationship with written texts, the media, and technologies. Consideringwriting as a technology, this text shows its articulations with the others in the current historical conditionsof college education in our country.The analysis shows the contrast between the crisis of a written culture, historically precarious in theColombian education, and the rising of the contemporaneous techno-culture, as a result of a culturaltransformation from which many of the reading and writing problems on behalf of the students are derived,problems the diagnosis and solutions of which transcend the boundaries of disciplinary researches, bethey linguistical, semiotic, or literary.